PEMBUATAN KOMPOSIT SERAT SERABUT KELAPA DAN RESIN POLYESTER SEBAGAI MATERIAL PEREDAM AKUSTIK - Suriadi, Suriadi; Balaka, Ridway; Hasanuddin, La (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
Noise pollution from noise is a classic promblem in Indonesia. This noise can be reduced by using anacoustic damper. Composite material made from coconut fiber fiber matrix is an alternative material forenvironmentally friendly acoustic damper because it utilizes agricultural waste material. This research hasmade composite based on coconut fiber fiber matrix with polyester resin. To increase the strength of coconutfiber fibers was first muffled in 2% NaOH solution for 3 hours. The composite made then tested the value ofsound absorption coefficient (????), composite damping test is done on kundst tube impedance tool equippedwith spekerr device,amplifer,power supllay,lettop,smartphone,oscilloscope,sound lever meter with inputfrequency 200,400,600 Hz. The result of Noise Absorption Coefficient (NAC) test of all polyester resincomposite test specimens in coconut fiber reinfercement have the highest absorption coefficient 0,50568 (????)at fractoin of 70:30% fiber volume with frequency of 600 Hz. While for the lowest sound absorption result0,503558 (????) with volume fraction of 70:30% fiber with frequency 200 Hz. The overall specimen can be madeas a damper because it has a sound absorption coefficient value >0.5Key word: Composite, acoustic damping, coconut fiber fibers and NAC.